Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1517/14728222.6.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factors in cancer: therapeutic possibilities

Abstract: The fibroblast growth factor (FGF) family of signalling molecules and its receptors (FGFRs) contribute to normal developmental and physiological processes. However, the subversion of this powerful growth stimulatory pathway has been implicated in the generation of a variety of pathological conditions. This review focuses on the role of FGF/FGFRs in cancer. The case will be made that this signalling pathway is associated with and functionally important for the growth of some human tumours. As such, FGF/FGFRs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 102 publications
1
36
0
Order By: Relevance
“…Indeed, FGF2 upregulation in melanoma cells (12) has been linked to melanoma progression (13) and is accompanied by the expression of FGFRs that trigger an autocrine loop of stimulation critical for the survival and growth of melanoma cells. In parallel, FGF2 induces a proangiogenic response by acting on FGFR1-expressing endothelial cells via a paracrine mechanism of action (8), thus supporting tumor growth and hematogenous dissemination of metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, FGF2 upregulation in melanoma cells (12) has been linked to melanoma progression (13) and is accompanied by the expression of FGFRs that trigger an autocrine loop of stimulation critical for the survival and growth of melanoma cells. In parallel, FGF2 induces a proangiogenic response by acting on FGFR1-expressing endothelial cells via a paracrine mechanism of action (8), thus supporting tumor growth and hematogenous dissemination of metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The FGF gene family encompasses 22 members (10) that exert their activity by binding to tyrosine kinase FGF receptors (FGFR) expressed by 4 distinct FGFR1 to FGFR4 genes (11). FGF2 expression is an important feature of melanoma cells (12) and it has been linked to tumor progression in melanoma and various other malignancies (13). FGF2 production is paralleled by the expression of FGFRs that trigger an autocrine loop of stimulation critical for the survival and growth of melanoma cells (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that members of the FGF family together with their transmembrane tyrosine kinase receptors (FGFR) may act as autocrine as well as paracrine (angiogenic) growth factors in many, if not all, solid tumors (26). FGFs act as mitogens and some members induce cell migration, angiogenesis, neurite outgrowth and cell survival (27).…”
Section: Fgfr1 Gene Status ------------------------------------------mentioning
confidence: 99%
“…27 One therapeutic intervention in signal transduction would be the stable formation of an incomplete (nonsignaling) complex to block cell replication for the treatment of cancer. 28,29 Insulin Signaling. Obesity and diabetes is a growing health problem in the developing world.…”
Section: Fgf Signal Transductionmentioning
confidence: 99%